Oversize fashion crochet : [6 cozy cardigans, pullovers & wraps designed with maximum style and ease] - Baca, Salena (Stackpole Books, 2023)
"Get ready for cool weather, fast! You'll be ready to cozy up in no time with these 6 crochet designs made with bulky yarn and big hooks. Designs include pullovers, cardigans, ponchos, and wraps in easy-to-wear, popular oversized fit"--